TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENANGGULANGAN PENYAKIT ISPA DI PUSKESMAS SEPASO TAHUN 2025 - Sriminarty Tambing; Maria Elvina Tresia Butar-Butar; Raymon Simanullang (Journal of Innovation Research and Knowledge, 2025)
This study aims to evaluate the level of public knowledge about the management of Upper Respiratory Tract Infections (ISPA) at the Sepaso Health Center in 2025. ISPA is a significant health problem in Indonesia, with a high incidence rate often caused by a lack of public knowledge about the prevention and treatment of this disease. Through this research, it is hoped that valuable information can be obtained to improve efforts to prevent and overcome ISPA in the future. The research method used is a survey with data collection through questionnaires distributed to the community in the Bengalon Health Center area. This research will also identify factors that affect the level of public knowledge about ISPA, as well as the effectiveness of educational programs that have been implemented by the Health Center. The majority of respondents were < 35 years old (37.5%), gender (66.7%), university education level (95.2%), working, (100%). The majority of knowledge levels are good (37.5%), the level of knowledge is sufficient >35 years old (72.7%), women (32.6%), elementary school (66.7%), working (39.4%), the level of knowledge is sufficient >35 years old (100%), women (100%), junior high school (63.6%), and RT mothers (50%).